Navigasi Budaya Digital Berbasis Kepemimpinan Profetik Pada Program Studi Manajemen Pendidikan Islam - Adi Nur Ali; Siti Aimah (JURNAL MANAJEMEN PENDIDIKAN, 2026)
NAVIGATION OF DIGITAL CULTURE BASED ON PROPHETIC LEADERSHIP IN THE ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM This study aims to analyze the digital culture navigation strategy based on prophetic leadership in the Islamic Education Management Study Program, KH University. Mukhtar Intercession Banyuwangi. The method used is qualitative with a case study approach. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation with purposive sampling techniques in determining informants. Data analysis applies an interactive model that includes data reduction, data presentation, and conclusion drawn, while data validation is ensured through triangulation of sources and techniques. The results of the study show that prophetic leadership successfully navigates disruption through the actualization of shiddiq, amanah, tabligh, and fathanah values in the form of integrated SIAKAD updates, anti-plagiarism curriculum, and e-learning optimization. The contribution of this research provides a tactical blueprint for Islamic universities in assimilating modern technology without reducing the cyber spiritual morality of the academic community.